Sino-African relations: a comparative case study analysis of the foreign policy objectives, internal factors and external factors influencing Sino -Namibian and Sino-South African relations - Shatona, Longeni Tunovaameni (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2025.